Explanations for the United States of America's dominance in basketball at the Beijing Olympic Games (2008) - Sampaio, J.; Lago, C.; Drinkwater, E. J. (Journal of Sports Sciences, 2010)
Anecdotally, the fast pace at which the USA men's basketball team played at the 2008 Olympics was the main reason for their dominance, although there is no way of quantifying what a fast pace is or how it contributed to point differentials. The aim of this study was to examine the game-related statistics that discriminate between fast- and slow-paced games, as well as to identify key performance factors relating to point differentials. We analysed game-related statistics for each quarter of the eight games played by the USA using a k-means cluster analysis to classify game pace using ball possessions per game quarter. We then tested for differences in game statistics between slow- and fast-paced game quarters using analysis of variance and discriminant analysis. How differences in game-related statistics affected point differentials was examined using linear regression. The largest structure coefficient between game paces for the USA was for recovered balls (0.33, P < 0.001). The biggest contributors to the point differences in games were recovered balls (16.9, P < 0.001) and field goals (22.2, P < 0.001). We conclude that when the USA play a fast-paced game, they are able to recover more balls from opponents that they then turn into effective field-goal shooting.